Verification Study On Response Analysis Of Truss Bridge Compression Members - Lilya Susanti (Rekayasa Sipil, 2016)
Finite element structural analysis of truss bridge model with 2-direction earthquake motion has more significant effect in decreasing the strutural capacity compared to 1-direction motion. The present paper focusses on the significancy investigation of 1-direction and 2-direction earthquake motion to the maximum stress and strain of the compression members. Finite element model of a full truss bridge system was employed. The numerical results were verified using some utimate stress and strain formulae. The result verified that the 2-direction earthquake motion has much more significant effect in decreasing the bridge capacity and the escalation of maximum stress and strain establish the non-linear lines with the ground motion magnification factor. The most severe buckling occured in the members located near the bearing support.